Tamoxifen as a new therapeutic tool for neutrophilic lung inflammation. Issue 1 (29th October 2015) - Perez, Barbara; Henriquez, Claudio; Sarmiento, Jose; Morales, Natalia; Folch, Hugo; Galesio, Juan S.; Uberti, Benjamin; Morán, Gabriel
Abstract: Background and objective: Neutrophilic asthma is an important disease subgroup, including patients with severe phenotypes and erratic responses to standard treatments. Tamoxifen (TX), a selective estrogen receptor modulator (SERM) used as treatment of human breast cancer, has been shown to induce early apoptosis of equine blood and bronchoalveolar lavage fluid (BALF) neutrophils in vitro. Equine recurrent airway obstruction (RAO) is a naturally occurring neutrophilic condition, closely related with human asthma. Our purpose was to investigate the therapeutic potential of tamoxifen in horses with neutrophilic lung inflammation. Methods: Twelve horses underwent acute lung inflammation through exposure to allergens known to cause RAO, after which they received treatment with either tamoxifen or dexamethasone. Outcome measures included evaluation of clinical signs, BALF cytology, and early apoptosis of blood and BALF neutrophils. Results: Tamoxifen treatment decreased BALF neutrophil counts (65.3 ± 19.38% before treatment; 7.6 ± 4.5% 2 days post‐treatment, ; and 13.6 ± 9.3% 5 days post‐treatment). A similar decrease was observed with dexamethasone treatment (48.6 ± 5.88% before treatment; 11.5 ± 8.1% 2 days post‐treatment; 14.6 ± 10.3% 5 days post‐treatment). Clinical and endoscopic scores improved in both treatment groups. Tamoxifen treatment significantly increased early apoptosis of peripheral blood neutrophils at 5 days post‐treatment (27.04 ± 15.2%), and in BALF neutrophils at 2 and 5 days post‐treatment (42.11 ± 11.67% and 48.98 ± 2.6%, respectively). Conclusion: Tamoxifen treatment in horses with induced acute pulmonary inflammation promoted early apoptosis of blood and BALF neutrophils, reduction in BALF neutrophils and improvement in the animals' clinical status. Abstract : Neutrophilic asthma includes patients with severe phenotypes, whose response to standard treatments may be erratic. Treatment with TX in an equine model of neutrophilic lung inflammation induced a significant increase of neutrophil early apoptosis in peripheral blood and BALF, and improvement of the animals' clinical condition.